Characterization, mechanical properties, and microstructural development of lunar regolith simulant-portland cement blended mixtures. (20th October 2020) - Neves, Juliana Moraes; Ramanathan, Sivakumar; Suraneni, Prannoy; Grugel, Richard; Radlińska, Aleksandra
Highlights: JSC-1A is a reliable filler/aggregate for use with portland cement. Despite the high amorphous content, JSC-1A is less reactive than most pozzolans. The pozzolanic reactivity of JSC-1A increases with fineness. Abstract: Lunar regolith simulant – JSC-1A is a basaltic powder compositionally similar to rock samples brought back from the moon by Apollo missions. This study describes JSC-1A as a potential construction material advancing the critical, prerequisite knowledge for the construction of shelters on the moon. A reactivity test based on isothermal calorimetry and thermogravimetric analysis was conducted on JSC-1A materials of different fineness. The results indicated that the finer portion could potentially be used as a supplementary cementitious material (SCM) of low reactivity, whereas the coarser fraction, which was considered inert, could be used as a filler/aggregate material (similar to sand). Four JSC-1A-portland cement blended pastes were tested as prospective binders. Some extent of portlandite consumption by JSC-1A in blended pastes was confirmed through thermogravimetric analysis. Blended mortar containing 75% JSC-1A and 25% portland cement developed over 30 MPa of compressive strength at 28 days of hydration and an increasing strength development over time was observed, as JSC-1A slowly reacted. Microstructural analysis of these mortars showed evidences of dissolution sites on JSC-1A and formation of different types of reaction products. The results presented and discussed in this research lengthen the directions for long-term space missions.